PURWARUPA SISTEM PERINGATAN DINI DAN KENDALI PINTU AIR BENDUNGAN DENGAN KENDALI P.I.D (PROPORSIONAL, INTEGRATIF, DERIVATIF) - , BENNI SAHPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to create a prototype of early warning system and dam sluicegate control by P.I.D control (proporsional, integratif, derivatif). To detect the water level and sluicegate used sensor SRF04. There are two sensors, sensor SRF04 (1) to detect the height of the sluicegate and sensor SRF04 (2) to detect water level. SRF04 sensor ( 2 ) detects the water level based on range of setpoint, then will be processed by the microcontroller. PWM output of the microcontroller by the PID control is embedded in the microcontroller will be forwarded to the motor driver circuit to drive the sluicegate are open and closed. Motor DC is used to drive the floodgates are open and close based on setpoint. The setpoint of the sluicegate is 5cm, 10cm, and 15cm. The system also will transmit information level and the status of water in the form of SMS based setpoint range of water levels used GSM modul. Setpoint range of water level is 0cm - 5cm, 5cm - 10cm, 10cm - 15cm, 15cm - 20cm. SMS delivery is done with a pause 1sms/40s, 1sms/30s, 1sms/20s, 1sms/10s based water level setpoint. The system will be send SMS with a pause 1sms/40s, 1sms/30s, 1sms/20s, 1sms/10s based water level setpoint. Alarm / buzzer will turn on when the water has reached the maximum. Result of PID constants from this research is Kp = 100 , Ki = 0.2 , Kd = 50. When reaching setpoint 10cm, the constants have the best response time compared with the other constants which rise time = 7,98 sec, settling time = 11,64 sec, steady state time = 11,76 sec. The results of the PID control would be used to open the sluicegate driven by motor DC to open and close with a low high-setpoint according to the height of the sluicegate which has been determined.